PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN TRUST TERHADAP KEPUASAN KONSUMEN PADA PT. POS INDONESIA CABANG SOLO - Sutarno, Achmad Fuat Khamali, Alwi Suddin & (Universitas Slamet Riyadi, 2018)
This study aims to determine and analyze the significance of the effect of product quality on customer satisfaction, to know and analyze the significance of the influence of service quality on customer satisfaction, and to know and analyze the significance of the influence of trust on consumer satisfaction. The population of this study are consumers who use services in PT. Pos Indonesia Branch Solo is not known exactly how many, the number of samples as many as 100 people with sampling techniques with convenience sampling technique. Technique of collecting data using questioner through validity and reliability test. Analysis technique through multiple regression analysis, t test, F test and R2. The analysis results obtained: (1) Quality of PT products. Pos Indonesia Branch Solo not has a significant effect on customer satisfaction; (2) Quality of service of PT. Pos Indonesia Branch Solo not has a significant effect on customer satisfaction; (3) Trust PT. Pos Indonesia Branch Solo has a significant effect on customer satisfaction. The conclusion of this research is there is significant influence of product quality, service quality, and trust to customer satisfaction at PT. Pos Indonesia Branch Solo. Keywords: Product quality, Quality of service, Trust, Consumer Satisfaction.